Zambia's Infrastructure : A Continental Perspective - Foster, Vivien; Dominguez, Carolina (World Bank, Washington, DC, 2017)
Infrastructure improvements contributed 0.6 percentage points to the annual per capita growth of Zambia's gross domestic product (GDP) over the past decade, mostly because of the exponential growth of information and communication technology (ICT) services. Poor performance of the power sector reduced the per capita growth rate by 0.1 percentage point. Simulations suggest that if Zambia's infrastructure platform could be improved to the level of the African leader, Mauritius, per capita growth rates could increase by two percentage points per year. Zambia's high generation capacity and relatively high power consumption are accompanied by fewer power outages than its neighbors. But Zambia's power sector is primarily oriented toward the mining industry, while household electrification, at 20 percent, is about half that in other resource-rich countries. Zambia's power tariffs are among the lowest in Africa and are less than half the level needed to accelerate electrification and keep pace with mining sector demands. Meeting future power demands and raising electrification rates will be difficult without increasing power tariffs. Zambia's infrastructure situation is more hopeful than that of many other African countries. Infrastructure spending needs, though large, are not beyond the realm of possibility, and Zambia's resource wealth and relatively well-off population provide a more solid financing basis than is available to many other countries. Zambia's infrastructure funding gap, though substantial, can be dramatically reduced through measures to stem inefficiencies and lower costs.